IMPACT OF THE ANNEALING TEMPERATURE OF IN2O3 FILMS ON THE PHOTOVOLTAIC CHARACTERISTICS OF A POLYMER SOLAR CELLS - Zeinidenov, A.K.; Аimukhanov, A.K.; Omarbekova, G.I.; Ilyassov, B.R. (KU Publ., 2022)
It is necessary to determine the effect of thermal annealing on morphology, absorption, and photoelectric properties for increase the efficiency of electronic transport of In2O3 films. The paper presents the results of a study the effect of the annealing temperature of In2O3 films obtained by spin-coating on the optical and photoelectrophysical characteristics of a polymer solar cell. It is established that an increase in the annealing temperature of films leads to an increase in the absorption and optical width of the band gap of the film. Has been determined the optimal annealing temperature of the films T = 300°C, at which the electrons in the photoactive layer has the maximum lifetime of charge carriers and a low probability of recombination. At this temperature is observed, the maximum value of the efficiency of polymer solar cell.
Keywords: In2O3; polymer solar cell; voltage characteristics; impedance spectra